(untitled) (Estudios Sociales, 2021)
This article seeks to rehearse a brief genealogy about the evaluative reason and those positions that in different ways seek to resist it. For this, an archival investigation was carried out taking Argentine education magazines from the end of the 19th century as a reference and exploring what contemporaneously they can accommodate their proposals regarding a critical approach to the problem. From a philosophical perspective, different textualities are analyzed that make it possible to raise two great moments in this essay: the first, dedicated to exploring the weight of pro-evaluative (or pro-exam) arguments and discussing its continuous passage in the evaluative time; the second, dedicated to rescuing the "counterweight" of counter-evaluative positions that collectively constitute a common struggle and trace ethical-political gestures that discontinue the synonymy installed by modernity/coloniality between education and evaluation. This last moment is presented as an evocative textual framework that offers a necessarily open end.